2020
DOI: 10.1016/j.xfre.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fertilization outcomes after preimplantation genetic testing for chromosomal structural rearrangements comparing fluorescence in-situ hybridization, microarray comparative genomic hybridization, and next-generation sequencing

Abstract: Objective: To compare in vitro fertilization (IVF) outcomes for preimplantation genetic testing for chromosomal structural rearrangements (PGT-SR) using various testing platforms. Design: Retrospective cohort. Setting: Large academic IVF center. Patient(s): Fifty-one balanced translocation carriers undergoing IVF with PGT-SR who completed a total of 91 cycles, including 31 fluorescence in-situ hybridization (FISH), 24 microarray comparative genomic hybridization (aCGH), and 36 next-generation sequencing (NGS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The genetic testing in this study was performed by NGS, it allowed to identify and screen for embryos with reduced viability such as mosaic embryos and those with partial aneuploidies or triploidy. Other studies revealed that NGS improves pregnancy outcomes versus array comparative genomic hybridization ( 14 ), there was a tendency towards a higher live birth rate for NGS testing in comparison with fluorescence in-situ hybridization and microarray comparative genomic hybridization ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic testing in this study was performed by NGS, it allowed to identify and screen for embryos with reduced viability such as mosaic embryos and those with partial aneuploidies or triploidy. Other studies revealed that NGS improves pregnancy outcomes versus array comparative genomic hybridization ( 14 ), there was a tendency towards a higher live birth rate for NGS testing in comparison with fluorescence in-situ hybridization and microarray comparative genomic hybridization ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to different methods of karyotyping, there are various genetic testing methods used for PGT-SR. A recently published study by Bartels et al. ( 9 ) describes differences in implantation rates and pregnancy outcomes depending on the PGT-SR technology used. The study finds NGS to provide superior outcomes compared with the use of FISH, and array comparative genomic hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis and diagnosis of translocations in adults and children are historically performed by Giemsa staining (G-banding) and/or fluorescence in situ hybridization (FISH) ( 6 , 7 ), with FISH providing a higher level of resolution. The identification of translocations present in PGT-SR embryos are normally tested by FISH, array comparative genomic hybridization, quantitative polymerase chain reaction (qPCR), single nucleotide polymorphism array, or next-generation sequencing (NGS) ( 8 , 9 ). The genetic testing method used for PGT-SR can significantly affect the outcome of the IVF cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next-generation sequencing (NGS) is a newer technology that is increasingly being used for PGT [8]. NGS has been shown to result in superior pregnancy outcomes compared with the use of fluorescence in situ hybridization, and array comparative genomic hybridization [9]. NGS has a high sensitivity and specificity for detecting the segmental and whole chromosome [10].…”
Section: Introductionmentioning
confidence: 99%